PENGARUH GAYA KEPEMIMPINAN, KEPERCAYAAN DAN KEMAMPUAN TERHADAP EFEKTIVITAS KEPEMIMPINAN WANITA (STUDI PADA PEMERINTAH DAERAH KOTA MATARAM) - Dwi Putri Yuliani (Master of Management, Mataram University, 2016)
This research is aimed at determining how significant the effect of leadership style, trust, and competence is on the effectiveness of women leader either partial or simultaneously. Besides that this resaerch is also aimed at determining which factor of the leadership style, trust, and competence dominantly affecting the effectiveness of women leader. The samples were 85 employees selected through proporsionated random sampling. They are coming from local government stajJingagencies, agricultural, fishery, and forestry extension agencies, local library and archive board of Mataram. The data were analyzed with multiple linear regressions. The research showed that (1) there is partially significant effect of leadership style, trust, and competence on the effectiveness of women leader in Mataram, (2) there is simultaneously significant effect of leadership style, trust, and competence on the effectiveness of women leader in Mataram, (3) Trust is the most dominant factor affecting the effectiveness of women leader in Mataram.Keywords: leadership style, trust, and competence, effectiveness of women leader